Thailand : Reducing Emissions from Motorcycles in Bangkok - World Bank (Washington, DC, 2014)
This report summarizes the findings of a study partially financed by the joint United Nations Development Programme (UNDP)/World Bank Energy Sector Management Assistance Programme (ESMAP). A plan was designed to phase out in-use old motorcycles in partnership with the government agencies and private sector (manufacturers and local banks). The report presents a plan to assist the Bangkok Metropolitan Administration ( BMA) to reduce emissions from two-stroke engine motorcycles in Bangkok. The report describes the two motorcycle clinics that were organized in Bangkok in May and July 2000 to improve the knowledge base, to promote awareness, to encourage interagency coordination and public-private partnerships, and to pilot the approach in generating lessons for the proposed Bangkok Motorcycle Upgrade Project (MUP). During these clinics, significant lessons were learned and observed on the issues of public and private sector involvement, the effectiveness of publicity campaigns and advertisements, interview questionnaire preparation and design, and the relevance of reconditioning for emissions.